Language of distance perception: cultural and linguistic implications in distance expression - Endsley, Tristan (The University of Edinburgh, 2011)
Do speakers that use different kinds of language representations to describe the same concept come to perceive and conceptualize the world in different ways? Particularly, what role does culture play in creating and defining our conceptualization of the physical and abstract domains of the human experience, in domains such as space, time and distance, and does it in fact determine the language is used to describe those conceptualizations? This study examined the effects of culture on influencing the language used to describe concepts of distance and whether the language used shapes how distances are perceived among different cultures. Following in a line of research aimed at the question of whether the linguistic representations used to represent concepts actually define how those concepts are perceived, especially within the natural world, the current study examines the specific parameter of culture in (1) dictating the type of language used to express the same physical space, and within a cultural group (2) manipulating and defining individual perceptions of space as it applies to the cognition of distance reasoning and expression. In two experiments, a survey and a navigation decision task examined several elements of culture and the impact it has in designating the type of language choices that are made, and found that culture does in fact influence the type of language that is chosen to describe distances. Furthermore it was found that the language used to describe distances reflects a cognitive perspective that influences reasoning in a navigation task.
The language of distance perception: cultural and linguistic implications in distance expression
Keywords: Distance Expression; Culture; Cognition; Spatial Reasoning